Neural generators involved in visual cue processing in children with attention‐deficit/hyperactivity disorder (ADHD). (26th November 2020) - Zarka, David; Leroy, Axelle; Cebolla, Ana Maria; Cevallos, Carlos; Palmero‐Soler, Ernesto; Cheron, Guy
Abstract: Event‐related potentials (ERP) studies report alterations in the ongoing visuo‐attentional processes in children with attention‐deficit/hyperactivity disorder (ADHD). We hypothesized that the neural generators progressively recruited after a cue stimulus imply executive‐related areas well before engagement in executive processing in children with ADHD compared to typically developed children (TDC). We computed source localization (swLORETA) of the ERP and ERSP evoked by the Cue stimulus during a visual Cue‐Go/Nogo paradigm in 15 ADHD compared to 16 TDC. A significant difference in N200/P200 amplitude over the right centro‐frontal regions was observed between ADHD and TDC, supported by a stronger contribution of the left visuo‐motor coordination area, premotor cortex, and prefrontal cortex in ADHD. In addition, we recorded a greater beta power spectrum in ADHD during the 80–230 ms interval, which was explained by increased activity in occipito‐parieto‐central areas and lower activity in the left supramarginal gyrus and prefrontal areas in ADHD. Successive analysis of the ERP generators (0–500 ms with successive periods of 50 ms) revealed significant differences beginning at 50 ms, with higher activity in the ventral anterior cingulate cortex, premotor cortex, and fusiform gyrus, and ending at 400–500 ms with higher activity of the dorsolateral prefrontal cortex and lower activity of the posterior cingulate cortex in ADHD compared to TDC. The areas contributing to ERP in ADHD and TDC differ from the early steps of visuo‐attentional processing and reveal an overinvestment of the executive networks interfering with the activity of the dorsal attention network in children with ADHD. Abstract : N200/P200 alterations in visuo‐attentional processing in ADHD was supported by a stronger contribution of the left visuo‐motor coordination area, premotor cortex, and prefrontal cortex in ADHD. Successive swLORETA ERP generators revealed higher activity in the ventral anterior cingulate cortex, premotor cortex, fusiform gyrus, dorsolateral prefrontal cortex, and lower activity of the posterior cingulate cortex in ADHD compared to TDC. Overinvestment of the executive networks interfering with the activity of the dorsal attention network in children with ADHD.